2003
DOI: 10.1097/00008390-200304000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the c-kit receptor in choroidal melanomas

Abstract: The KIT gene encodes c-kit, a transmembrane receptor that has tyrosine kinase activity and plays a role in haematopoiesis, gametogenesis and melanogenesis. The c-kit protein is found in normal cutaneous and choroidal melanocytes, and there is evidence that expression is lost in melanoma. Expression of c-kit was analysed in 57 paraffin-embedded sections of choroidal melanoma specimens and three choroidal melanoma cell lines using immunochemistry and Western blotting. Of the tumour specimens, 75% stained positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 25 publications
4
36
1
Order By: Relevance
“…Indeed, clinical studies using imatinib in melanoma patients with confirmed KIT-activating mutations have yielded promising results. [10][11][12][13] Although it is arguably premature, the reported high frequency of KIT overexpression in ocular melanoma (63-91%) [17][18][19][20][21][22] has led to an interest in the use of imatinib therapy for this melanoma subtype. In initial studies, however, overexpression of KIT protein in ocular melanoma does not appear to imply response to imatinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, clinical studies using imatinib in melanoma patients with confirmed KIT-activating mutations have yielded promising results. [10][11][12][13] Although it is arguably premature, the reported high frequency of KIT overexpression in ocular melanoma (63-91%) [17][18][19][20][21][22] has led to an interest in the use of imatinib therapy for this melanoma subtype. In initial studies, however, overexpression of KIT protein in ocular melanoma does not appear to imply response to imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Arising from melanocytes of the choroid, iris, ciliary body, and conjunctiva, ocular melanomas have been reported to express KIT (CD117) at frequencies between 63 and 91%. [17][18][19][20][21][22] KIT mutations, however, have only been reported in one conjunctival tumor. 8 Given the low frequency of KIT mutations (o1%) in ocular melanoma, it is not surprisingly that recent studies have failed to demonstrate the clinical efficacy for imatinib mesylate therapy in unselected patients.…”
mentioning
confidence: 99%
“…We have demonstrated that c-Kit is activated by exogenous SCF during normal uveal melanocyte (NUM) proliferation and probably also during pathogenic bilateral and diffuse uveal cell proliferation (34). We have also shown that c-Kit is expressed in 75% of primary choroidal melanomas (35). Mitotic activity and c-Kit immunoreactivity are positively correlated, suggesting that c-Kit is involved in the transformation of normal uveal melanocytes into tumor cells (35).…”
mentioning
confidence: 88%
“…We have also shown that c-Kit is expressed in 75% of primary choroidal melanomas (35). Mitotic activity and c-Kit immunoreactivity are positively correlated, suggesting that c-Kit is involved in the transformation of normal uveal melanocytes into tumor cells (35). However, the roles of SCF/ c-Kit and of the downstream intracellular signaling pathway have been evaluated during the transformation of normal uveal melanocytes.…”
mentioning
confidence: 94%
“…Notably, UM was not included in the abovementioned study analyzing KIT activation in melanoma (6). This is particularly puzzling, as it has been shown that 75% of primary UM exhibited KIT positivity with a significant positive association with mitotic activity (8).…”
mentioning
confidence: 99%